2016
DOI: 10.17507/jltr.0706.19
|View full text |Cite
|
Sign up to set email alerts
|

Language and Power: The Use of Persuasive Techniques in Iran and U.S. President Speeches

Abstract: The present article is about language and power, focuses on the speechmaking skills, and using persuasive techniques such as Simile and metaphor, Mixed metaphor or simile, Extended metaphor, Allusion, Lists of three, Repetition, Parallelism, Puzzled or redundant questions, Alliteration and Wordplay. For the sake of better analysis certain elements of this ability, a comparison between Iran President Mr. Rouhani and U. S. President Mr. Obama is made. Two speeches of two presidents are selected. The first two ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 3 publications
1
11
0
1
Order By: Relevance
“…Many research studies have been carried out on persuasion in different genres such as political discourse, advertisements and literary work, etc. (Boden 2004;Mikayelyan 2011;Flergin 2014;Ko 2015;Rabab'ah and Khawaldeh 2016;Rezaei and Nourali 2016, among International Journal of Linguistics ISSN 1948-5425 2019 others). Boden (2004) investigated Shakespeare's persuasive dialogues.…”
Section: Studies On the Persuasive Strategies Used In Different Genresmentioning
confidence: 99%
See 1 more Smart Citation
“…Many research studies have been carried out on persuasion in different genres such as political discourse, advertisements and literary work, etc. (Boden 2004;Mikayelyan 2011;Flergin 2014;Ko 2015;Rabab'ah and Khawaldeh 2016;Rezaei and Nourali 2016, among International Journal of Linguistics ISSN 1948-5425 2019 others). Boden (2004) investigated Shakespeare's persuasive dialogues.…”
Section: Studies On the Persuasive Strategies Used In Different Genresmentioning
confidence: 99%
“…In the same vein, Rezaei and Nourali (2016) investigated the use of persuasive strategies by Iran President Mr. Rouhani and the U. S. former President Mr. Obama. The researchers stated that although both presidents can persuade, their persuasive techniques differ dramatically.…”
Section: Studies On the Persuasive Strategies Used In Different Genresmentioning
confidence: 99%
“…Several studies have dealt with the use of different rhetorical devices in political discourse (e.g., Capone, 2010;Cheng, 2006;Rezaei & Nourali, 2016;Tekin, 2008;Wei, 2000;Wei et al, 2008, etc.). For instance, adopting Lakoff and Johnson's (1980) proposal of metaphor in a case study, Wei (2000) explored the metaphorical usage of campaign slogans in the 1996 presidential campaign in Taiwan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using Moore's (2003) theoretical framework, Rezaei and Nourali (2016) compared the use of persuasive rhetorical strategies in political speeches by the presidents of Iran and the U.S., Rouhani and Obama. The results of their study showed no significant difference between the two presidents' use of persuasive techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Power relations should be regarded as discursive, and social relations of power can be exercised and negotiated in and through discourse for every political action that can be prepared, accompanied, influenced and delivered by language. Politicians may achieve their political goals by physical enforcement but there would be another way that is more tactful-the use of persuasive techniques in order to persuade people to act in a special way they intend (Jalilifar & Alavi, 2011 as cited in Norali & Rezaei, 2016).…”
Section: Introductionmentioning
confidence: 99%